When occupational self efficacy and intrinsic motivation influence on job satisfaction and job performance - Unik Dwi Lestari (IJHCM (International Journal of Human Capital Management), 2022)
This study aims to determine the effect of occupational self-efficacy on intrinsic motivation, job satisfaction and job performance. In addition, the influence of intrinsic motivation on job satisfaction and job performance. This research is a descriptive quantitative study made using the structural equational modeling (SEM) method. Data collection was used by distributing online questionnaires. The population of this study are employees of private companies in the areas of Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek). The sampling method used is purposive sampling with criteria that have worked for 2 years and over. The results of this study prove that there is a positive influence between occupational self-efficacy and intrinsic motivation, job satisfaction and job performance. Then it also proves that there is a positive influence between intrinsic motivation on job satisfaction but not on job performance.